2017
DOI: 10.3389/fpls.2017.01067
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment and Patch Establishment by Seed in the Seagrass Posidonia oceanica: Importance and Conservation Implications

Abstract: Seagrasses are declining globally, and deeper understanding is needed on the recruitment potential and distribution of new populations for many threatened species to support conservation planning in the face of climate change. Recruitment of Posidonia oceanica, a threatened seagrass endemic to the Mediterranean, has long been considered rare due to infrequent flowering, but mounting evidence demonstrates that the species is responding to a changing climate through greater reproductive effort. Due to the fragme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 71 publications
1
22
0
Order By: Relevance
“…Sexual reproduction has long been considered to be less important than clonal growth for seagrass propagation, due to the occurrence of large clones (Reusch, Boström, Stam, & Olsen, 1999). However, there is a growing recognition that recruitment by seeds is also important in maintaining seagrass populations, as revealed by high clonal diversity (Ruggiero, Reusch, & Procaccini, 2005) or visible seed production and recruitment events in the field (Balestri, Vallerini, & Lardicci, 2017;Xu et al, 2018). In this study, high clonal diversity was found in both plots using a short sampling interval of 1 m, which was slightly lower than the previous population level studies (Yu et al, 2018).…”
Section: Contribution Of Clonal Growth and Sexual Reproductionmentioning
confidence: 99%
“…Sexual reproduction has long been considered to be less important than clonal growth for seagrass propagation, due to the occurrence of large clones (Reusch, Boström, Stam, & Olsen, 1999). However, there is a growing recognition that recruitment by seeds is also important in maintaining seagrass populations, as revealed by high clonal diversity (Ruggiero, Reusch, & Procaccini, 2005) or visible seed production and recruitment events in the field (Balestri, Vallerini, & Lardicci, 2017;Xu et al, 2018). In this study, high clonal diversity was found in both plots using a short sampling interval of 1 m, which was slightly lower than the previous population level studies (Yu et al, 2018).…”
Section: Contribution Of Clonal Growth and Sexual Reproductionmentioning
confidence: 99%
“…However, factors governing stable states of seagrass beds are not well-known. Although some studies of seagrass ecosystems quantitatively link disturbance regimes with seagrass responses on a landscape-scale, the link may be location dependent (Duarte and Sand-Jensen, 1990; Kirkman and Kuo, 1990;Fonseca and Bell, 1998;Kendrick et al, 1999;Turner et al, 1999). Several authors clearly define environmental thresholds that may drive seagrass coverage from one state to another (Carr et al, 2010;Maxwell et al, 2015Maxwell et al, , 2016Moksnes et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…With increasing coastal tourism and exploitation, G. littoralis have become endangered (Kerbiriou et al , 2008; Yang and Zhang, 2010; Balestri et al , 2017). Glehnia littoralis are observed to persist well only along sandy coasts, where surging seawater acts as a natural and efficient vector to ensure normal population dispersal (Yang et al , 2017).…”
Section: Discussionmentioning
confidence: 99%